The Thermo Techno Modern Analytical Equipment for Research and Industrial Laboratories - Khokhlov, S.V.; Smyrny, M.A. (Science and Innovation, 2024)
A brief overview of some models of Thermo Techno analytical equipment and possible areas of their application is given. Thermo Techno Corporation was established in 2000 as a part of representative office of Thermo Fisher Scientific International Corporation, a world leader in manufacturing analytical equipment. Thermo Techno is a unique company which has its integrated approach to providing the user with support in solving its tasks, which includes a series of steps: setting of analytical assignment, selection of effective analytical methods, sample delivery and preparation, as well as data transfer and archiving.